Pharmacokinetics of Heparin in Healthy and Obese Subjects and in Combination with Dihydroergotamine - Beermann, Björn; Lahnborg, Gordon (Thrombosis and Haemostasis, 1981)
Heparin (5000 IE s.c., 5000 IE i v, 200 IE/kg i v) was given to healthy volunteers without and with 0.5 mg dihydroergotamine (DHE) i v to test whether DHE influences the kinetics of heparin. The anticoagulant (200 IE/kg) was also administered to obese subjects. Heparin was assayed using a chromogenic substrate for activated factor X.The plasma levels of heparin did not differ whether given concomitantly with DHE or not. Halflife of heparin was also uninfluenced of DHE demonstrating that the beneficial effect of DHE on postoperative thromboembolism is not caused by interaction with the pharmacokinetics of heparin.The plasma levels of heparin were significantly higher in the obese subjects than in the normal ones. The halflife of the drug averaged 2.13 h in the obese subjects and 1.36 h in the normal subjects (p<0.02). It was concluded that the heparin dosage should be calculated in terms of estimated ideal weight.
Keywords: Dihydroergotamine; Drug interaction; Heparin; Thromboembolism